👤

what number must be added to 3a + 6b -52 to give up -7a +2b + 17?

Sagot :

Answer:

-10a-4b+69

Step-by-step explanation:

3a+6b-53 + -10a-4b+69 = -7a+2b+17

Answer:

-10a - 4b + 69

Step-by-step explanation:

Let the number be x.

[tex]\rm 3a + 6b - 52 + x = -7a + 2b + 17[/tex]

[tex]\implies \rm x = (-7a + 2b + 17) - (3a + 6b - 52)[/tex]

[tex]\implies \rm x = -7a + 2b + 17 - 3a - 6b + 52[/tex]

[tex]\implies \rm x = -7a - 3a + 2b - 6b + 17 + 52[/tex]

[tex]\implies \boxed{ \rm x = -10a - 4b + 69}[/tex]

#CarryOnLearning